گەشەپێدانی هۆشیاری سیاسی شیكردنەوەیەكی تیۆری - مجید, پ.ی.د پەیمان عبدالقادر; رحیم, خوێندكاری ماسته‌ر: ئاری انور (Sulaimani Journal for Humanities, 2023)
The existence of awareness in any society is one of the indicators of the vitality of this society, and the development of political awareness as a process in society indicates the continuity of this vitality, so we want to talk in this research about a problem that exists in society, namely the development of political awareness, and the main problem in the research is What is meant by the development of political awareness? The aim of this study is to search for the sources that cause the development of political awareness, so that members of society can find a way to develop their political awareness, and participate in the political process effectively, and we also want to highlight those difficulties and obstacles that are an obstacle to the development of political awareness, and the importance of research lies In knowing the sources of developing political awareness, in order for us to have a role and participation in the political process, the descriptive analytical approach was used for this purpose.
Keywords: Keywords Development Awareness Political Awareness Development Political Awareness